(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
This article elucidates features of branching and seasonal development in Salvia aethiopis L. in the region of Nothern Prichornomorye. All the sprouts have complete development cycle with all buds being vegetative. The four types of sprout rosettes are described. The sprout seasonal development does not fit the annual climarythm completely.